Longitudinal Development of Explosive Leg Power from Childhood to Adulthood in Soccer Players - Deprez, D.; Valente-Dos-Santos, J.; Coelho-e-Silva, M. J.; Lenoir, M.; Philippaerts, R.; Vaeyens, R. (International Journal of Sports Medicine, 2015)
The aim of the this study was to investigate the development of explosive leg power by using 2 similar jumping protocols (countermovement jump and standing broad jump) in 555 Belgian, high-level young soccer players, aged between 7 and 20 years. The total sample was divided into 3 longitudinal samples related to growth and maturation (pre-teenchildhood: (6–10 years;), early adolescence: (11–16 years;) and late adolescence: (17–20 years)), and 6 multilevel regression models were obtained. Generally, both jumping protocols emphasized that chronological age, body size dimensions (by means of fat mass in the late childhood and early adolescence groups, fat-free mass in the late adolescence group and stature – (not for CMJ in late childhood group) and fat mass in the late childhood and early adolescence groups, and fat-free mass in the late adolescence group) and motor coordination (one item of a 3-component test battery) are longitudinal predictors of explosive leg power from childhood to young adulthood. The contribution of maturational status was not investigated in this study. The present findings highlight the importance of including non-specific motor coordination in soccer talent development programs.
Keywords: football; talent identification; multilevel regression; countermovement jump; standing broad jump